Rezar, educar, proteger : el Salmo 1 en la documentación papirológica procedente del Egipto tardoantiguo - Chapa, Juan (Chronique d’Égypte, 2024)
Abstract The testimonies to Psalm 1 from late antique Egypt reflect the enduring popularity of this text, though its specific uses often remain uncertain. As the opening psalm of a book (Psalms) widely employed in both liturgical and educational contexts, it is plausible that some of these testimonies were originally copied for such purposes. Furthermore, given its promise of “bearing fruit in due season,” it is not surprising that Psalm 1 was also invoked to secure divine protection, potentially holding special significance for pregnant women.